Upaya Peningkatan Pariwisata Indonesia Melalui ASEAN Connectivity 2015 - Paramitha Utami, Kade Yasinta; Fasisaka, Idin; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   This study aims to analyze Indonesia's efforts to improve tourism through the ASEAN Connectivity 2015. ASEAN Connectivity 2015 is a framework of cooperation ratified by ASEAN member countries in an effort to improve intra-ASEAN connectivity. The method used in this research is descriptive qualitative research method. This study answers the problem that answers the question of how Indonesia's efforts in improving tourism through the 2015 ASEAN Connectivity cooperation framework. This study uses data collected through various sources including literature studies, news, and reports. The data in this study were analyzed through the concept of economic development and the concept of regional cohesion in the science of International Relations. The results of this study see that Indonesia is utilizing increased connectivity within the AC 2015 framework as an effort to improve tourism.   Keyword : ASEAN Connectivity, tourism, economic development, regional cohesion